Use of computational methods to identify new ligands of ROR𝛾 - DiProperzio, Anthony (Kansas State University, 2021)
Retinoid-related orphan receptor 𝛾 (ROR𝛾) is called an orphan receptor because for a while it was not known whether this nuclear receptor had any endogenous ligands, but as of now, a myriad of sterols as ROR𝛾 natural ligands have been discovered. It is the lineage-specific master transcription factor that is also the only nuclear receptor established to enhance T helper 17 differentiation and restrain T regulatory cell differentiation. T helper 17 cells are the major proinflammatory cells that produce cytokines that cause responses such as tissue inflammation and clearance of extracellular pathogens. T helper 17 cells can also produce a particular cytokine called Interleukin-17 which induces autoimmune responses. For the past 10 years, many new synthetic ROR𝛾 agonists and antagonists have been developed. There are still remaining questions to understand ROR𝛾. To increase understanding of the ROR𝛾 signaling pathway and to speed the drug design of ROR𝛾 agonists, computational methods were used to study the structure of ROR𝛾 and its agonist drug design. These computational methods included virtual screening, molecular docking, and fragment-based drug discovery to formulate a chemical starting point for the identification of new ligands of ROR𝛾. More information on the activated state of this transcription factor was obtained by studies of these agonists and ROR𝛾. The results of this research consisted of chemical fragments that bound different areas of the active site of the ligand binding domain of ROR𝛾. In addition, new compounds were discovered that have different scaffolds compared to known ROR𝛾 bioactives and are currently awaiting experimental testing in the laboratory.
Keywords: Computational retinoid-related orphan receptor